ANALYSIS OF THE SELECTION OF THE ALKI STATES FOR HANDLING CRIMINAL ACTIONS OF VIOLATIONS BY THE MULTI CRITERIA DECISION MAKING APPROACH (CASE STUDY ALKI II) - Petrus Indra Cahyadi; Avando Bastari; As'ad Aris M (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT The incidents of criminal offenses at sea that often occur in Indonesian waters greatly affect the credibility and authority of the Indonesian people in the eyes of the international community. Based on existing data, the number of criminal offenses at sea in Indonesian waters is the largest in the world, especially in ALKI II waters. This condition of course has a negative impact on the Indonesian government. There are several studies that take the theme of selecting locations with the Analytic Hierarchy Process (AHP) and Geographic Information System (GIS) methods. Wang (2009) states, although the AHP method is more widely used in building a decision-making system, this method has drawbacks, namely that it does not consider uncertainties and doubts in decision making. Therefore, Fenton & Wang (2006) argue that fuzzy-set theory can be used to overcome the limitations of AHP. This study assesses the location selection using Fuzzy AHP and TOPSIS to reduce decision uncertainty. This research can help determine the best Indonesian Navy base from several existing bases, especially those around ALKI II waters. This base will then serve as an aju base for KRI and personnel carrying out maritime security operations in the context of handling criminal offenses at sea. In the research area which is limited to ALKI II waters, there are 7 Indonesian Navy bases that can be used as alternatives, namely Lanal Palu, Lanal Kendari, Lanal Tolitoli, Lanal Nunukan, Lanal Sangatta, Lanal Kota Baru, Lanal Banjarmasin. From the weighting and ranking results, the Banjarmasin Navy Base was selected as the best Aju base, namely from a scale of 0-1, with a weight value of 0.8442. Keywords : Selection of Indonesian Navy bases, Fuzzy AHP, Topsis